Measuring Children's Decision-Making Involvement Regarding Chronic Illness Management - Miller, Victoria A. (Oxford University Press, 2012)
Objectives To develop a measure of decision-making involvement in children and adolescents with cystic fibrosis, diabetes, and asthma. Methods Parent–child dyads completed the Decision-Making Involvement Scale (DMIS) and measures of locus of control and family communication. DMIS items were subjected to exploratory and confirmatory factor analysis (CFA). Temporal stability and construct validity were assessed. Results The parent form was reduced to 20 items representing five factors. CFA showed that the five factors were an acceptable fit to the parent- and child-report data. Internal consistency values ranged from 0.71 to 0.91. Temporal stability was supported by moderate–substantial intraclass correlation coefficients. DMIS subscales were associated with child age, child locus of control, and family communication. Conclusions The DMIS can be used to inform our understanding of the transition to greater independence for illness management. Additional research is needed to examine outcomes of decision-making involvement, including treatment adherence and responsibility.